Research on Poverty Reduction and Livelihoods for the Poor: Theoretical Approaches - Le Hoang Kiet (International Journal of Educational and Life Sciences, 2024)
Poverty reduction plays an important role in the socio-economic development strategy of countries around the world. The article provides an overview of the theoretical approaches to poverty reduction and livelihoods for the poor globally today. The first part introduces the concept of poverty in the world. The second part will present in detail the theoretical approaches to poverty and livelihoods for the poor worldwide. The research results provide in-depth understanding of the concept of poverty in the world, theoretical approaches to poverty and livelihoods for the poor globally, contributing to a comprehensive understanding of poverty research methods and towards providing information for governments and policymakers to build a theoretical framework for sustainable poverty reduction for the country.